OPTIMIZING THE MARKETING MIX TO ENHANCE THE COMPETITIVENESS OF FRESHWATER FISH HATCHERIES - Nurhaeni Sikki; Atventus Nainggolan; Ratna Deli Sari; Huda Binti Ibrahim (Multifinance, 2026)
This study analyzes the optimization of the marketing mix to improve the competitiveness of freshwater fish hatcheries, with a case study of Haji Aep’s hatchery in Warung Jambe Village, Karang Tengah District, Cianjur. The research aims to identify the strengths and weaknesses of existing marketing strategies and formulate alternative strategies to enhance competitiveness. The study applied a qualitative descriptive approach supported by SWOT analysis to examine internal and external factors. Data were collected through observation, interviews, and documentation. The results indicate that product quality, pricing strategy, distribution channels, and promotional activities play a crucial role in strengthening competitiveness. The findings further suggest that collaboration with local communities, government support, and market expansion are essential for sustaining business growth. This research concludes that optimizing the marketing mix can significantly increase the market competitiveness of freshwater fish hatchery enterprises.